What Obstetrician-Gynecologists Think of Preconception Care - Morgan, Maria A. (Springer US, 2006)
Objectives: To describe obstetrician-gynecolog-ists’ opinions of preconception care (PCC) and ascertain patient uptake for this service. Methods: A questionnaire was mailed to 1105 ACOG members in August 2004. Results: There was a 60% response rate. Most physicians think PCC is important (87%) and almost always recommend it to women planning a pregnancy (94%); 54% do so with women who are sexually active. Around a third (34%) thought their patients usually do not plan their pregnancies and 49% said very few pregnant patients came in for PCC. Of those who obtain PCC, they were believed to do so more likely to assure a healthy pregnancy (83%) than because of an elevated risk for birth defects (20%). Of 11 issues presented, cigarette smoking and folic acid supplementation were rated the most important for PCC counseling; exercise and environmental concerns were the least important. Conclusions: Physicians are willing to provide PCC but few patients are accessing such services.